Containing (un)American bodies : race, sexuality, and post-9/11 constructions of citizenship - Bloodsworth-Lugo, Mary K. (Value Inquiry Book Series, 2010)
"The authors argue that queer, black, brown, and foreign bodies, and the so-called threats they represent, such as immigration reform and same-sex marriage, have been effectively linked with terrorism. These awful conflations are enduring and help to explain the contradictions of contemporary U.S. politics. We are far from a post post-9/11 world." Ronald R. Sundstrom, Associate Professor, Department of Philosophy, The University of San Francisco, United States"If you want to understand how a new biopolitics of citizenship is containing bodies of the nation by re-inscribing sex and race into it and how this new biopolitics is being resisted you must read this book." Engin F. Isin, Professor, Department of Politics and International Studies, The Open University, UK.